ECONOMIC ANALYSIS OF TEMPEH INDUSTRY HOUSEHOLDS IN BEJI VILLAGE, JUNREJO SUB-DISTRICT, BATU CITY - Asgar, Forestio; Agnes Quartina Pudjiastuti; Khoirunnisa, Ninin (Journal of Agricultural Socio-Economics (JASE), 2024)
The household economy of the tempeh industry is inseparable from several blocks of production equations, work time, income, and expenses. Generally, tempeh makers use imported soybeans as the main raw material because it has more suitable characteristics compared to local soybeans. This study aimed to analyze the household economy at home in the tempeh industry in Beji Village, Junrejo Subdistrict, Batu City based on the four blocks, namely production, work time, income, and expenses. The population in this study were active tempe crafters in Beji Village, totaling 131 crafters. Thus using the Simple Randon Sampling method which is done randomly. The data analysis method uses simultaneous equation analysis, formulated into a simultaneous equation with the two-stage least squares (2SLS) method. The results showed that based on the results of parameter estimation on the production block, work time, income and expenses that the R2 value can be explained while the Fcount value shows that it simultaneously affects